2002
DOI: 10.1111/j.1095-8649.2002.tb01850.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of granulocytes in haematopoietic tissues of Rhizoprionodon lalandii

Abstract: Granulocytes of the epigonal and Leydig organs of Rhizoprionodon lalandii were identified and classified into three different cell types, type I and type II eosinophils and neutrophils. The development of these cells in the haematopoietic tissues was dynamic, demonstrated by nuclear immunopositivity for the proliferating cell nuclear antigen (PCNA) proteins and was regulated by various cytokines, including the transforming growth factor -1 (TGF 1 ). The expression pattern of these cells was heterogeneous among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The highly granular appearance reported here for the epigonal organ leukocytes of Prionace in many ways resembles the observations made in the lymphomyeloid tissues of other similarly caught elasmobranchs (Hine & Wain, ,b; Pacheco et al. ), but differs from the rather non‐granular nature of the epigonal organs of the six sexually immature nurse sharks kept for several weeks in holding tanks (Fange & Mattison, ). It should also be noted that the parameters of stress physiology and blood properties measured in long‐line‐captured P. glauca compare favorably with the baseline values of the unstressed sandbar and spiny dogfish sharks (Marshall et al.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The highly granular appearance reported here for the epigonal organ leukocytes of Prionace in many ways resembles the observations made in the lymphomyeloid tissues of other similarly caught elasmobranchs (Hine & Wain, ,b; Pacheco et al. ), but differs from the rather non‐granular nature of the epigonal organs of the six sexually immature nurse sharks kept for several weeks in holding tanks (Fange & Mattison, ). It should also be noted that the parameters of stress physiology and blood properties measured in long‐line‐captured P. glauca compare favorably with the baseline values of the unstressed sandbar and spiny dogfish sharks (Marshall et al.…”
Section: Discussionsupporting
confidence: 83%
“…Using the immunolocalization of the conserved nuclear factor, PCNA (its immunohistochemistry was previously optimized for shark tissues; Pacheco et al. ; McClusky, , ), it was shown that granule‐lacking leukocytes exclusively infiltrated those cysts that were partially filled with spermatozoa and present in the testis after the wave of wide‐spread MNC apoptotic death in summer‐breeding males (McClusky, ). Blue sharks caught 2 months later possessed, however, fully recovered testes containing numerous intact and spermiating spermatozoal cysts but with no trace of leukocyte infiltration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These selective methods for collagen also demonstrate that the stroma of this organ is made up a fine web of reticular fibres where a large number of cells of the parenchyma are supported, forming a true haematopoietic tissue. This fibrillary web appears to be common in the HK of all teleosts and is also present in other types of organs with haematopoietic function found in Chondrichthyes (Sailendri & Muthukkaruppan, 1975; Sorensen et al , 1997; Pacheco et al , 2002).…”
Section: Discussionmentioning
confidence: 75%
“…For the detection of the expression of the surface antigens DRO45 for T cells, CD68 for macrophages, monocytes and their precursors, and lysozyme for granulocytes, an indirect immunoenzymatic method was used in three steps, utilizing the biotin–streptavidin– peroxidase complex. Sections (3 µm) were placed on silanized slides and dried at 37° C. The slides were then deparaffinized, hydrated, treated in 0·3 M citrate buffer, pH 6·0, placed in a microwave at maximum power for 30 min (UNIFESP/EPM protocol; http://www.unifesp.br) and incubated in an aqueous solution of H 2 O 2 at 50% (Merck) for 15 s to block endogenous peroxidase activity (Pacheco et al , 2002). After washing in distilled H 2 O, the sections were treated in 0·1 M PBS, pH 7·4, for 10 min and incubated with primary antibody diluted 1:80 for CD45RO, 1:100 for CD68, and 1:100 and 1:2000 for lysozyme in bovine serum albumin (BSA) at 1% in PBS overnight, at 3° C in a humidified chamber.…”
Section: Methodsmentioning
confidence: 99%